Morphological and Phenotypic Peculiarities of Cytospheres Forming in Adrenal Cell Cultures of Neonatal Piglets in Normal and Low Adhesive Conditions - Plaksina, Ekaterina M.; Sidorenko, Olga S.; Bozhok, Galina A. (Problems of Cryobiology and Cryomedicine, 2015)
N/A